Anti-inflammatory and analgesic effects of Kaihoujian throat spray, and therapeutic mechanism in acute pharyngitis: involvement of the NF-κB/COX-2 pathway and formula deconstruction strategy - Shi, Hui; Zhang, Jinhe; Zhang, Liyan; Dong, Xiu; Liu, Chang; Liu, Xiongwei; Zhou, Ying; Feng, Tingting (Frontiers in Pharmacology, 2025)
IntroductionKaihoujian (KHJ) throat spray is a traditional formula derived from the Miao ethnic minority in China, which is highly effective in treating acute pharyngitis and tonsillitis. This study aimed to investigate the anti-inflammatory and analgesic effects, and therapeutic mechanism, of KHJ in acute pharyngitis. The study hypothesized that the integrated composition of KHJ exerted superior therapeutic effects through synergistic actions.MethodsThe study employed a formula deconstruction strategy, comparing the complete KHJ formula with its individual components. The compatibility of KHJ was assessed through high performance liquid chromatography fingerprinting. Its anti-inflammatory and analgesic properties were evaluated using models of xylene-induced edema, acetic-acid permeability, and hot plate and writhing tests. An acute pharyngitis model was established in rats using 10% ammonia to assess the alterations in behavioral, histological parameters, and serum levels of inflammatory cytokines. Western blot analysis was performed to analyze the expression of cyclooxygenase-2 (COX-2) and nuclear factor kappa B (NF-κB) pathway proteins. Molecular docking was utilized to investigate the interactions between bergenin, matrine, oxymatrine, and macaine of KHJ and inflammatory targets COX-2, NF-κB p65, and p-NF-κB p65.ResultsThe fingerprint and assay results indicated no significant changes in the number of chromatographic peaks of KHJ before and after compatibility, though the elution of indicator components did interact. KHJ’s whole formula outperformed separated components in anti-inflammatory and analgesic assays. In pharyngitis, KHJ reduced pathological damage, downregulated interleukin 1β (IL-1β), interleukin 6 (IL-6), prostaglandin E2 (PGE2), and elevated interleukin 10 (IL-10). Western blot revealed KHJ suppressed COX-2 and p-NF-κB p65/NF-κB p65 expression. Molecular docking supported strong binding affinities between KHJ’s active compounds and inflammatory targets.ConclusionThis study confirmed the potent anti-inflammatory and analgesic effects of the Miao medicine KHJ and its efficacy in treating acute pharyngitis. It was novel in reporting the complete KHJ formula as significantly superior to its individual components, thereby underscoring the vital role of integrated formulation design. Furthermore, the therapeutic effect was mechanistically associated with inhibition of the COX-2/NF-κB signaling pathway. These findings provide a scientific foundation for the clinical application of KHJ and validate the rationale of Miao medicine compatibility.